Anonymous Group Message Authentication Protocol for LTE‐based V2X Communications. Issue 2 (29th January 2018) - Liu, Dongxiao; Ni, Jianbing; Lin, Xiaodong; Shen, Xuemin (Sherman)
Abstract: Cellular technologies, in particular the current long‐term evolution (LTE) and future 5G, are suitable for implementing vehicle‐to‐everything (V2X) services, due to the existing network infrastructure, device‐to‐device (D2D) communication capability, and guaranteed end‐to‐end delay. In LTE‐based V2X (LTE‐V), vehicle grouping plays an important role for improving LTE spectrum utilization and providing group‐oriented proximity‐based services (ProSe). However, the flourishing of LTE‐V group communications introduces unique privacy challenges. In this letter, the state‐of‐art standardization and research efforts are first reviewed, and their limitations are identified on achieving trajectory privacy for LTE‐V group communications. Then, an efficient and anonymous group message authentication protocol is proposed to support message batch verification. Security analysis and performance evaluation demonstrate the feasibility of the proposed protocol.